Neonatal Symptoms in Pediatric Idiopathic Growth Hormone Deficiency: Prevalences and Insights - Giorgio Sodero; Donato Rigante; Clelia Cipolla (Children)
Background: Growth hormone deficiency (GHD) is one of the primary endocrine-related causes of short stature in pediatric patients; while neonatal GHD symptoms are well-documented in populations with known genetic and/or organic causes, their exact prevalences in pediatric patients categorized as having idiopathic GHD remains unclear. Materials and Methods: We retrospectively analyzed the medical records of patients with idiopathic GHD followed at the Pediatric Endocrinology Unit of the Fondazione Policlinico Universitario A. Gemelli IRCCS starting from January 2010. We analyzed information from 190 patients with idiopathic GHD and examined the prevalences of the most common neonatal signs and symptoms of neonatal GHD. We also included an age- and sex-matched control group that consisted of patients without a confirmed diagnosis of GH deficiency to assess significant differences in the frequencies of neonatal symptoms between the two cohorts. Results: Regarding neonatal GHD symptoms, the prevalence was the highest for hypoglycemia (n = 53, 27.9%), which was managed through the intravenous administration of glucose in 21 out of 53 cases. Prolonged jaundice that lasted more than 5 days was observed in 37 patients (19.5%) and required phototherapy in 20 out of 37 patients, while exchange transfusion was not performed in any patient. Hyperglycemia and feeding difficulties (n = 17, 8.9%) were less frequent, while the other symptoms were relatively rare. Compared with the control group, the prevalence of hypoglycemia was significantly higher in the GHD patient group (p-value = 0.000016). Conclusions: In our cohort of pediatric patients with idiopathic GHD, the prevalences of neonatal signs and symptoms of GHD was low, except for neonatal hypoglycemia observed in 27.9% of the analyzed patients. Although these are not specific signs of idiopathic GHD, it is beneficial to investigate this information in the medical history during the clinical assessment of the child.